Analisa Q.S. An-Nur Ayat 58 Tentang Larangan Anak Masuk Kedalam Kamar Orang Tua dalam Pandangan Para Mufassir - San Putra; Syahputra, Eka Bayu (Jurnal Landraad, 2023)
The role taught by parents to children regarding manners should start early. Because the process of child development is determined by the education obtained from the surrounding environment. This article discusses the differences in the interpretation of the QS. An-Nur verse 58 according to commentators. Among them according to the views of Ahmad Mustafa Al-Maraghil, Jalaluddin Al Mahalli in Tafsir Al-Jalalain, and Quraish Shihab. In the discussion of QS. An-Nur verse 58 according to the commentators there are several views regarding the interpretation of the verse. The views of each of these figures are related to the prohibition of children entering their parents and also teaching about the manners contained therein and the steps to get used to children asking permission before entering a room and using other people's things.